A study of conformational variation of temperature-dependent PEEK molecular structures subject to stretching speeds by molecular dynamics simulations - Yi, Taeil (Journal of mechanical science and technology, 2022)
Rapid prototyping is one of the core technologies for industry 4.0. Various studies in academia and industry have focused on producing the most qualified printing outputs by tuning operation processes, selecting appropriated printing products, etc. In addition, test & evaluation processes of the final products are essential to validate the performance of outputs. Many mechanical components in a system are under different pressure distributions depending on working environment conditions. However, mechanical characteristics of printing products subject to thermal constraints have rarely been studied based on microscopic viewpoints. This study focuses on the microscopic tensile elongation phenomena of pre-built PEEK (poly-ether-ether-ketone) structures at different working temperatures. A coarse-grained molecular model is employed to save computation time and resources. Conformational variations of PEEK structures and dependent behaviors of individual molecules are characterized by using the radial pair distribution functions, the dimensional relative variations of the radius of gyrations, the number density profiles, and averaged tetrahedral order parameters to elucidate deformation properties of microscopic structures at different uniaxial stretching speeds at three given temperatures using systematic molecular dynamics simulations.